RECRUITMENT AND SELECTION PRACTICE ON INDONESIA STATE-OWNED ENTERPRISE: A LITERATURE REVIEW - Jafar Basalamah; Muhammad Herdiansyah Syahnur; Abdurrahman Basalamah (Manajemen Bisnis, 2020)
In modern days recruitment and selection practices has become a challenge within the developing countries. Various companies struggling with personnel challenges due to increasing competent applicants. The labor market focuses on factors affecting recruitment and selection practices on organizational performance and it becomes a challenge for corporate owners. Because of the fact, attracting qualified, skilled and experienced candidates is important and urgent. In this note, relative HR strategy practices bring changes to organizational growth and impact organizational and corporate performance. The purpose of research was to explore factors affecting the recruitment and practice of selection on the company's performance. However, this research provides useful insight into critical literature, evidence and contributes to finding gaps in recruitment and practice selection at the company's performance in particular state-owned enterprises. Therefore, these studies review past literature and secondary data gathered from different sources such as official publications from each authority, website, journal, and books. This critical review emphasized that the recruitment and selection practices were manipulated in the recruitment sector of state-owned enterprise. Therefore, the company faced great difficulties to provide a professional public service.